The genomic sequence of Exiguobacterium chiriqhucha str. N139 reveals a species that thrives in cold waters and extreme environmental conditions - Ana Gutiérrez-Preciado; Carlos Vargas-Chávez; Mariana Reyes-Prieto; Omar F. Ordoñez; Diego Santos-García; Tania Rosas-Pérez; Jorge Valdivia-Anistro; Eria A. Rebollar; Andrés Saralegui; Andrés Moya; Enrique Merino; María Eugenia Farías; et al. (PeerJ, 2017)
We report the genome sequence of Exiguobacterium chiriqhucha str. N139, isolated from a high-altitude Andean lake. Comparative genomic analyses of the Exiguobacterium genomes available suggest that our strain belongs to the same species as the previously reported E. pavilionensis str. RW-2 and Exiguobacterium str. GIC 31. We describe this species and propose the chiriqhucha name to group them. ‘Chiri qhucha’ in Quechua means ‘cold lake’, which is a common origin of these three cosmopolitan Exiguobacteria. The 2,952,588-bp E. chiriqhucha str. N139 genome contains one chromosome and three megaplasmids. The genome analysis of the Andean strain suggests the presence of enzymes that confer E. chiriqhucha str. N139 the ability to grow under multiple environmental extreme conditions, including high concentrations of different metals, high ultraviolet B radiation, scavenging for phosphorous and coping with high salinity. Moreover, the regulation of its tryptophan biosynthesis suggests that novel pathways remain to be discovered, and that these pathways might be fundamental in the amino acid metabolism of the microbial community from Laguna Negra, Argentina.